Mothers' Within‐Marriage Economic Prospects and Later Food Security: Does Marital Outcome Matter?. Issue 3 (27th September 2017) - Men, Fei
Abstract : Single mother households are among those most susceptible to food insecurity, yet little do we know about its reason. By looking at the role of marital dissolution, this study examines whether within‐marriage economic prospects are related to posterior food security differently for recently divorced mothers and their continuously married counterparts. Regression analyses on recent Survey of Income and Program Participation data reveal that college diploma is related to lower risk of food insecurity for married and divorced mothers alike. On the other hand, severe disabilities and more births given in the past are associated with greater increase in food insecurity risk for recently divorced mothers than for their continuously married counterparts. Results of this study demonstrate the importance of education to mothers' food security overall and highlight the particular challenge faced by divorced mothers with severe disability or multiple children.